2016
DOI: 10.1088/0964-1726/25/9/095011
|View full text |Cite
|
Sign up to set email alerts
|

Sensing of damage and substrate stress in concrete using electro-mechanical impedance measurements of bonded PZT patches

Abstract: The user has requested enhancement of the downloaded file.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…Wang et al 24 investigated the effects of axial load on the RMSD index of SA sensors embedded in concrete. Narayanan and Subramaniam 25,26 studied the influence of stress and damage on the RMSD index and examined that the RMSD index increases with the load-induced damage without the influence of stress. These studies indicated that there is a relationship between the RMSD index and the structural damage, and the RMSD is a suitable index to estimate the damage of concrete.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al 24 investigated the effects of axial load on the RMSD index of SA sensors embedded in concrete. Narayanan and Subramaniam 25,26 studied the influence of stress and damage on the RMSD index and examined that the RMSD index increases with the load-induced damage without the influence of stress. These studies indicated that there is a relationship between the RMSD index and the structural damage, and the RMSD is a suitable index to estimate the damage of concrete.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have attempted to monitor impedance response-induced damage from PZT sensors placed on the surface of concrete structures [ 16 , 24 , 25 ]. The surface-mounted sensors could detect impedance signatures induced by local damage near the surface; however, they were not sensitive enough to monitor variation in the impedance responses that were induced by incipient damage in the anchorage zone [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Practical applications of the RMSD index for damage evaluation require an understanding of the influence of the damage on the signal response of bonded PZT sensors. Narayanan and Subramaniam [ 27 ] decoupled the effect of stress and damage using the normalized conductance signature as a quantitative measurement and pointed out that the RMSD increases consistently with the increase of damage when the applied stress is removed. Lim et al [ 28 ] found that the equivalent damping values increase with the increase of the damage severity and the RMSD response exhibits the equivalent damping change.…”
Section: Introductionmentioning
confidence: 99%